COVID-19, Economic Impact, Mental Health, and Coping Behaviors: A Conceptual Framework and Future Research Directions - Lu, Xiaoqian; Lin, Zhibin (Frontiers in Psychology, 2021)
The covid-19 pandemic has caused serious economic and social consequences. Recent research shows that the pandemic has not only caused a physical health crisis, but also caused many psychological and mental crises. Based on the contemporary cognitive-behavioral models, this article offers a conceptual analysis of how the pandemic affects individual mental health and coping behaviors from the perspective of individual economic status, individual context, and social context. The analysis shows that: 1) The pandemic has led to increased economic uncertainty, increased unemployment and underemployment pressure, increased income uncertainty, and different degrees of employment pressure and economic difficulties; 2) These difficulties have stimulated different levels of mental health problems, ranging from perceived insecurity (environmental, food safety, etc.), worry, fear, to stress, anxiety, depression, etc. The mental health deterioration varies across different groups, with the symptoms of psychological distress are more obvious among disadvantageous groups; 3) Mental health problems have caused behavior changes, and various stress behaviors such as protective behaviors and resistive behaviors. Future research directions are suggested.